Aquatic plant community in porto primavera reservoir - Pitelli,R.L.C.M. (2014)
Aiming to identify the populations of aquatic plants present in the Porto Primavera reservoir and evaluate the behavior of Hydrilla verticillata colonization of this water body a survey was carried out in 2007. The data was based on presence or absence, only were assessed the presence or absence of the species and the data were subjected to cluster analysis to establish differences in distribution and occurrence of populations. The community of aquatic plants showed 24 species distributed in 16 botanical families. Cyperaceae and Pontederiaceae were the most representative in terms of species richness. The submerged macrophyte Hydrilla verticillata showed the highest frequency of occurrence in the water body, showing a different behavior from the other populations of the water body. Species like Eichhornia crassipes, Eichhornia azurea, Typha dominguensis and Oxycaryum cubense also showed different behavior in relation to other populations within the community, forming large populations in lagoons and backwater areas.